New flavone from the leaves of Neea theifera (Nyctaginaceae) - Rinaldo, Daniel [UNESP]; Rodrigues, Clenilson M. [UNESP]; Rodrigues, Juliana [UNESP]; Sannomiya, Miriam [UNESP]; Dos Santos, Lourdes C. [UNESP]; Vilegas, Wagner [UNESP] (FapUNIFESP (SciELO), 2007)
Neea theifera Oerst. (Nyctaginaceae) is widely used in Brazilian folk medicine for the treatment of gastric ulcers and inflammation. Phytochemical investigation of the leaves of Neea theifera afforded the isolation of the new flavone luteolin-7-O-[2″-O-(5‴-O-feruloyl)-β-D-apiofuranosyl]- β-D-glucopyranoside (1) besides the eight-known compounds vitexin, isovitexin, isoorientin, orientin, vicenin-2, chrysoeriol, apigenin and luteolin. Their chemical identification was established by NMR spectroscopic methods including 2D-NMR, as well as UV and ESI-MS analyses. ©2007 Sociedade Brasileira de Química.
Keywords: Flavone; Luteolin-7-O-[2″-O-(5‴-O- feruloyl)-β-D-apiofuranosyl]- β-D-glucopyranoside; Neea theifera; Nyctaginaceae